Toward a Harmonic Relationship between Humans and Nature: A Humanist Reinterpretation of Early Confucian Philosophy - Luque-Moya, Gloria (University of Ljubljana Press, 2023)
We are living in an era in which the world is being turned into an object to be exploited and nature into a storehouse. From environmental pollution and deforestation to toxic waste and the depletion of resources, the Earth is in trouble and we need to act. To address this environmental crisis, I propose to recover early Confucian philosophy because it can be used to develop a more desirable way of interacting with the environment. Confucian philosophy conceives a kind of humanism that promotes a harmonious relationship between people and nature. Thus, this article attempts to describe a distinctive attitude towards nature and the role of humans that we can find in early Confucianism as a way of rethinking our current ecological concerns.
Keywords: Confucio; Cosmos; Harmony; Confucius; Dao; Tian; Tianxia